FOOD DEMOCRACY - Labatjo, Rahma (JOURNAL HEALTH AND NUTRITIONS, 2017)
ABSTRACT Democracy values in context of food systems reflect the equality in food choices, information availability, sustainability, involvement and greater satisfaction. In fact, development of food industry tends to lead people away from the truth concept of democracy. Farmers hardly play in food supply chain since their roles have been replaced by sophisticated food manufacturers. Their essential roles in food system have been overtaken by other actors which belong to industrialised food system such as large supermarket and food retailers. This means that equality as the truth concept of democracy has been limited. This essay describes the comparison between two major food supply sites namely large supermarket and farmers market. This essay examines the concepts of ?food? and ?democracy? in both sites, and provides further exploration of how the implementation of ?food democracy? in both sites. Keywords:Food, Democracy, Market ABSTRAK Nilai demokrasi dalam konteks sistem pangan mencerminkan kesetaraan dalam pilihan makanan, ketersediaan informasi, keberlanjutan, keterlibatan dan tingkat kepuasan yang lebih tinggi. Pada kenyataannya, perkembangan industri makanan cenderung membuat orang menjauh dari konsep demokrasi. Petani hampir tidak berperan dalam rantai pasokan makanan karena peran mereka telah digantikan oleh produsen makanan yang canggih. Peran penting mereka dalam sistem pangan telah digantikan oleh sektor lain yang tergabung dalam sistem pangan industri seperti supermarket besar dan pengecer makanan. Ini berarti bahwa persamaan hak sebagai konsep demokrasi telah dibatasi. Esai ini menggambarkan perbandingan antara dua lokasi penyediaan makanan utama yaitu supermarket besar dan pasar petani. Esai ini mengkaji konsep 'makanan' dan 'demokrasi' di kedua lokasi tersebut, dan memberikan eksplorasi lebih lanjut tentang bagaimana penerapan 'demokrasi pangan' di kedua lokasi tersebut. Kata kunci: Makanan, Demokrasi, Pasar